Wednesday

August 20, 2014

August 20, 2014

Posted by **Jim** on Tuesday, April 14, 2009 at 10:20pm.

- Math -
**Reiny**, Tuesday, April 14, 2009 at 10:23pmI do it this way:

1. switch the x and y variables to get

x = 2y + 3

2. solve this new equation for y

2y = x - 3

y = (1/2)x - 3/2

some people solve the original for x fist, then switch the variables.

-makes no difference, same number of steps, same work, same result.

**Related Questions**

Calculus - F(x) = 1-x and g(x) = 1/x These functions have the property that f = ...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

Algebra - I have to find the inverse function of f(x)=3-4x. I got y=3-x/4 for ...

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

Math 3 - Find the inverse of the function f(x) = 5 – e^(x-1). Determine the ...

pre calculus - Find the inverse of the function below. Graph the function below ...

College Algebra - Find the inverse of the function below. Graph the function ...

inverse - If f(x)=cosx + 3 how do I find f inverse(1)? Thanks y = cos(x) + 3 the...

precalculus - Find the inverse of the function below. Graph the function below ...

Maths B - (a) What is the inverse of the function y = 3x2 ? (b) On the same set ...